Retroperitoneoscopic resection with preoperative selective embolization and indocyanine green fluorescence visualization of vessels in kidney cancer - Resetniak, S. (KIDNEYS, 2023)
Background. Currently, kidney cancer is considered one of the most common oncological pathologies, accounting for 2–3 % of all cancers. In 2018, the total number of primary renal cell carcinoma patients in Ukraine was 4,805 cases, with 1,878 patients dying from this disease. Surgical treatment is the only way for 68 % of patients with localized kidney cancer. The main question remains unanswered — an effective surgical treatment of patients with localized renal cell carcinoma. Our aim was to study the kidney function parameters in localized kidney cancer after retroperitoneoscopic resection with preoperative selective embolization compared to standard kidney resection using thermal ischemia. Materials and methods. Data of 65 patients with localized kidney cancer who underwent nephron-sparing surgery were analyzed. They were divided into two groups. The first one included 40 people with localized kidney cancer who underwent standard organ-sparing surgery with duration of thermal ischemia of less than 20 minutes. The second group consisted of 25 patients with localized kidney cancer who underwent computed tomography with renal vessels reconstruction in the preoperative stage. Branch of the renal artery that feeds the area of the kidney with the tumor was identified. As a next step, selective embolization was performed. Retroperitoneoscopic resection was carried out the next day with fluorescence imaging in the infrared light using indocyanine green. Results. Analysis of the data shows that renal function after surgery for local cancer in case of retroperitoneoscopic resection with preoperative selective embolization of renal vessels is more functionally suitable compared to kidney resection using thermal ischemia. Conclusions. Our data suggest that superselective X-ray vascular embolization and intraoperative indocyanine green fluorescence in the surgical treatment of localized kidney cancer has significant advantages over the standard method of surgical treatment.